Kounis and Takotsubo, Two Syndromes Bound by Adrenaline: The “ATAK” Complex - Ravi Vazirani Ballesteros; Juan Carlos Gómez Polo; Carmen Olmos; Isidre Vilacosta (Case Reports in Cardiology)
Background. The term “ATAK” complex has been coined by the association of adrenaline, takotsubo, anaphylaxis and Kounis syndrome. We present an uncommon case of an “ATAK” complex with biphasic onset and a midventricular takotsubo pattern. Case Summary. A 50-year-old male was brought to the emergency department in anaphylactic shock. He had progressive exertional dyspnea and angina for the past 2 days. The intravenous administration of adrenaline for anaphylactic shock resulted in chest pain and concerning ECG repolarization findings. The patient was immediately transferred to the catheterization laboratory. Coronary angiography showed a midventricular ballooning pattern without significant coronary stenosis, with subsequent recovery during hospitalization, suggestive of takotsubo syndrome. The allergy tests remained inconclusive for the trigger. Discussion. Adrenaline-mediated stress is the link between these two entities, in which Kounis syndrome itself or anaphylactic shock treatment (adrenaline) are potential triggers for takotsubo syndrome.